THE LAW ENFORCEMENT AGAINST ILLEGAL FISHING IN THE INDONESIAN EXCLUSIVE ECONOMIC ZONE (ZEEI) NORTH NATUNA - Iswan, Muhammad Nur Hadi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2023)
Illegal fishing is a serious threat to the sustainability of marine resources in the Indonesian Exclusive Economic Zone (ZEEI), especially in the North Natuna region. This research aims to examine the regulations adopted by the Indonesian Government, regarding state boundaries in the North Natuna region which intersect with the sovereignty of other countries as well as the law enforcement process in the context of illegal fishing in the Indonesian Exclusive Economic Zone. The research method used is normative legal research in the form of library research with a conceptual approach and a statutory approach. The data sources used are statutory regulations and other literature related to the authority of the Indonesian Navy in enforcing the law regarding the crime of illegal fishing in North Natuna. The research results found that the state must act wisely and appropriately to ensure that its sovereign territory is maintained and protected from various kinds of potential disturbances that threaten, in this case illegal fishing in North Natuna. In an effort to resolve the problem of illegal fishing in the North Natuna Indonesian Exclusive Economic Zone (ZEEI), it is necessary to emphasize the diplomatic aspects carried out by the Indonesian Navy towards countries whose territories intersect on international borders. The use of the military as a last resort to protect the sovereign territory of the Unitary State of the Republic of Indonesia, in this case becomes a concept about how the Indonesian state respects the sovereignty of other countries. Keywords: Illegal Fishing, Law Enforcement, TNI AL, North Natuna.